2020
DOI: 10.1080/21655979.2020.1840731
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis to screen key prognostic genes in the breast cancer tumor microenvironment

Abstract: Increasing evidence has shown that the tumor microenvironment (TME) plays an important role in tumor occurrence and development and can also affect patient prognosis. In this study, we screened key prognostic genes in the breast cancer (BC) TME by analyzing the immune and stromal scores of tumor samples to detect differentially expressed genes (DEGs) and also constructed a TME-related prognostic model. First, we obtained mRNA-Seq and related clinical information for patients with BC from The Cancer Genome Atla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…However, the role and mechanism of GAD1 in CCA remains poorly defined. Killer cell lectin-like receptor B1 (KLRB1), also named as CD161, has been reported as a prognostic gene in many cancers [25][26][27]. For example, Qin et al showed that high expression of KLRB1 was associated with good overall survival in early cervical squamous cell carcinoma patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role and mechanism of GAD1 in CCA remains poorly defined. Killer cell lectin-like receptor B1 (KLRB1), also named as CD161, has been reported as a prognostic gene in many cancers [25][26][27]. For example, Qin et al showed that high expression of KLRB1 was associated with good overall survival in early cervical squamous cell carcinoma patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study based on public databases established a tumor microenvironment-related signature model to predict the prognostic features of BC [ 26 ]. However, metabolism-associated lncRNA signatures are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have highlighted the value of analyzing the immune cell infiltration of the tumor microenvironment when conducting prognostic assessments of breast cancer patients. Ye et al screened key prognostic genes in the breast cancer tumor microenvironment by analyzing the immune and stromal scores of tumor samples and also constructed a tumor microenvironment-related prognostic model [ 43 ]. Chemoresistance is a major barrier to breast cancer patient treatment that is often associated with disease recurrence and death [ 7 , 8 , 44 ].…”
Section: Discussionmentioning
confidence: 99%